2020
DOI: 10.1002/1873-3468.14000
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback and modern anti‐cancer strategies targeting the ER stress response

Abstract: Endoplasmic reticulum (ER) stress is a cell state in which misfolded or unfolded proteins are aberrantly accumulated in the ER. ER stress induces an evolutionarily conserved adaptive response, named the ER stress response, that deploys a self-regulated machinery to maintain cellular proteostasis. However, compared to its well-established canonical activation mechanism, the negative feedback mechanisms regulating the ER stress response remain unclear and no accepted methods or markers have been established. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 157 publications
(182 reference statements)
1
6
0
Order By: Relevance
“…Analysis of TCGA, GEO databases, and human tissue samples demonstrated a robust positive correlation between AURKA and increased UPR/ER stress in EAC. Recent studies indicated that IRE1α, PERK, and ATF6 are essential ER stress sensors, regulating the balance between cell survival and death during ER stress through UPR [33]. Our data not only indicated a remarkable increase in UPR proteins in EAC cells but also showed the critical prosurvival role of IRE1α compared with the other two primary ER stress sensors, PERK and ATF6.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Analysis of TCGA, GEO databases, and human tissue samples demonstrated a robust positive correlation between AURKA and increased UPR/ER stress in EAC. Recent studies indicated that IRE1α, PERK, and ATF6 are essential ER stress sensors, regulating the balance between cell survival and death during ER stress through UPR [33]. Our data not only indicated a remarkable increase in UPR proteins in EAC cells but also showed the critical prosurvival role of IRE1α compared with the other two primary ER stress sensors, PERK and ATF6.…”
Section: Discussionsupporting
confidence: 62%
“…As we showed the co-overexpression of AURKA and UPR key proteins, our data indicated that AURKA induced IRE1α levels and phosphorylation in EAC cells. IRE1α and its downstream sXBP1 promote cell survival during ER stress in several malignancies [33,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the triad stress responses of nucleus, ER, and mitochondria also induce oxidative damage, DNA mutations, angiogenesis, and metabolic changes, if sustained in chronic inflammation, conducive to cell malignant transformation and cancer growth (9)(10)(11). The inhibition of ER stress by chemical compounds has demonstrated effective in the preclinical and clinical trials of multiple tumors (12,13).…”
Section: Introductionmentioning
confidence: 99%